THE ACHAEMENID ADMINISTRATIVE SYSTEM IN EGYPT DURING THE REIGN OF DARIUS 1 (522-486 BC) - Alio, Siraj; Jameel, Hivi (Humanities Journal of University of Zakho, 2025)
In the mid-sixth century BC, the Achaemenid Persians came to power, bringing about major changes in the Middle East. They destroyed the Median state in 550 BC and established a new state. Their early kings, such as Cyrus II and his son Cambyses, pursued a policy of expanding the state's borders, and soon this new state was able to expand the country's borders, and the states of Lydia, Babylon, and later Egypt became part of this state. The Achaemenids ruled Egypt for 132 years in two phases. The first phase (525-402 BC) established the 27th dynasty in the country, and the second phase (342-332 BC) established the 31st dynasty under Artaxerxes III. According to Herodotus, this country was appointed as the sixth satrap. Egypt was important due to its geographical location and the presence of the Nile River, the variety of agricultural products, and the Achaemenid kings, especially Darius I, who wanted to dominate Egypt for trade between the East and the West, and hence, this country was of particular importance to the state. Therefore, the Achaemenid kings, one after another, intended to seize this country. This article is based on archaeological observations and recent historical research on the changes in administrative, economic, and social structures in Egypt during Persian rule and the impact of these two civilizations on each other.